Respuesta :
[tex]\\ \rm\Rrightarrow \sqrt{x²-10x+25}[/tex]
[tex]\\ \rm\Rrightarrow \sqrt{x²-5x-5x+25}[/tex]
[tex]\\ \rm\Rrightarrow \sqrt{x(x-5)-5(x-5)}[/tex]
[tex]\\ \rm\Rrightarrow \sqrt{(x-5)(x-5)}[/tex]
[tex]\\ \rm\Rrightarrow \sqrt{(x-5)^2}[/tex]
[tex]\\ \rm\Rrightarrow\pm (x-5)[/tex]
Solution set(for x-5)
- {-10,-9,-8,-7,-4,-3,-2,-1,0}
for 5-x
- {0,-1,-2,-3,-4,-5,-6,-7,-8,-9,-10}
Answer:
First, simplify the expression under the square root sign by factoring:
[tex]\implies x^2-10x+25[/tex]
[tex]\implies x^2-5x-5x+25[/tex]
[tex]\implies x(x-5)-5(x-5)[/tex]
[tex]\implies (x-5)(x-5)[/tex]
[tex]\implies (x-5)^2[/tex]
Therefore:
[tex]\implies \sqrt{x^2-10x+25}=\sqrt{(x-5)^2}[/tex]
[tex]\implies \sqrt{x^2-10x+25}=\pm(x-5)[/tex]
[tex]\implies \sqrt{x^2-10x+25}=|x-5|[/tex]
As the domain is -5 ≤ x < 5, then:
[tex]\implies y=-x+5[/tex]
and the range is 0 < y ≤ 10